«Ադամի արարումը» թե՞ «Հին աւուրցն Աստուած». Դանիել մարգարեի վախճանաբանական տեսիլքը Նորավանքում - Գրիգորյան, Տիգրան (Մատենադարան)
The purpose of this study is to analyze an Armenian monument of the 12th–14th centuries, the western portal of the porch of Holy Noravank‘. The bás-relief of one of the tympanums that adorn the porch of the Church of Stepanos the Prophet is an exceptional example in early medieval Christian art. An analysis of the composition and its iconography allows to assume that this is a depiction of the Last Judgment. The iconography of the Ancient of Days is based on Daniel’s eschatological vision and is a symbiosis of Biblical and apocryphal texts which complement each other in content. The Apostolic epistles and the Revelation of John also contribute to the interpretation of this scene. Целью данного исследования является анализ армянского памятника XIIXIV вв., западного портала гавита (притвора) Нораванка. Барельеф одного из тимпанов гавита церкви св. Стефана Первомученика – уникальное явление в средневековом христианском искусстве. Анализ истории изучения этой композиции, а также рассмотрение иконографии памятника позволяет предположить, что в порталe гавита Нораванка изображен Страшный суд. Иконография “Ветхого днями” основана на эсхатологическом видении Даниила и представ ляет синтез библейских и апокрифических текстов, дополняющих друг друга по содержанию. Кроме того, пониманию этой сцены способствуют новозаветные апостольские послания и Откровение Иоанна Богослова.
Keywords: Հուշարձաններ; Հայ եկեղեցու պատմություն